2018
DOI: 10.1111/jocn.14172
|View full text |Cite
|
Sign up to set email alerts
|

Positive effect on patient experience of video information given prior to cardiovascular magnetic resonance imaging: A clinical trial

Abstract: Video information prior to examinations can be an easy and time effective method to help patients cooperate in imaging procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 42 publications
(66 reference statements)
3
28
0
1
Order By: Relevance
“…The index results are in line with previous studies, which have indicated that the education approach and familiarization with medical equipment and technics can greatly improve the performances of diagnostic and therapeutic approaches [16][17][18][19]. For example, a recent study by Ahlander et al [20] indicated that video given before cardiovascular MRI helps patients relax during the imaging. Hayat et al [17] found that a patientcentered educational video improves bowel preparation quality and may reduce the possibility of a repeat procedure in patients with screening colonoscopy.…”
Section: Discussionsupporting
confidence: 88%
“…The index results are in line with previous studies, which have indicated that the education approach and familiarization with medical equipment and technics can greatly improve the performances of diagnostic and therapeutic approaches [16][17][18][19]. For example, a recent study by Ahlander et al [20] indicated that video given before cardiovascular MRI helps patients relax during the imaging. Hayat et al [17] found that a patientcentered educational video improves bowel preparation quality and may reduce the possibility of a repeat procedure in patients with screening colonoscopy.…”
Section: Discussionsupporting
confidence: 88%
“…Four different questionnaires, used in earlier studies where patient anxiety in connection with MRI has been evaluated 20,21 were used to characterize the patients. Hospital Anxiety and Depression scale (HAD) is developed in two parts, one measuring anxiety and one depression, seven items each 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Single items: Patient "experience" and "worry" during the examination were graded on a ten-point scale by patients and staff independently. The items have been used in previous MRI-study 21 . All staff members had extensive experience in performing MRI and were trained by the lead author how to use the assessment scale before the start of the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations